IMPROVING STUDENTS READING COMPREHENSION BY APPLYING PRE-QUESTIONING TECHNIQUE ( An Experimental Study at the Second Grade of SMAN 1 Glumpang Tiga) - Hanifah Thohidah; Mustakim Sagita; Jamaliah Jamaliah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
The objective of the study is to find out whether does the pre-questioning technique improve the students reading comprehension or not .The population of this research is the second grade of SMAN1 Glumpang Tiga. The sample of this study are one class was as experimental class (XI- IIS) where the writer applied Pre-Questioning technique in teaching learning activity, which consist of 20 students and the other one was as control class (XI-MIA 3) which taught by applying other technique, consisted of 20 students including . The instrument used in this study was a set of written test which was used for pre test and post test. Pre-test was given before the writer held an experimental teaching. Post test was given after the writer did an experimental teaching. The result of this research showed that in experimental class the mean of pre-test score (O1) was 55,10, the mean of post-test (O2) was 73,30 ,Furthermore in control class the mean of pre-test score (O1) was 53,80 , the mean of post test (O2) was 55,20 . It indictates that there was significance progression between students’ pre-test and post-test score in experimental class after teaching reading comprehension by applying pre-questioning technique. Or from the table 7 ( in the table of independent sample test ) we can see the significant value (sig) in the experimental class was 0,000 0.05, so there is an increase in students' reading comprehension which is very significant on the reading comprehension by applying pre-questioning technique. It accepted the alternative hypothesis while rejected the null hypothesis. Base on the data analysis, showed that applying pre-questioning technique was significantly improve the students’ reading comprehension.